2001
DOI: 10.4081/jlimnol.2001.1.263
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sediment contamination using six toxicity assays

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…1992) to 997 mg.kg -1 in 1996 (and the maximum values increased from 1978 to 2440 mg.kg -1 ) . Several toxicity tests ran in the years following liming (1992)(1993)(1994)(1995)(1996)(1997)(1998) confirmed that the sediments were contaminated enough to induce either a direct short term mortality or sublethal effects on crustacean species (Rossi and Beltrami, 1998;Beltrami et al, 1999;Barbero et al, 2001;Baudo et al, 2001b;Burton et al, 2001). This likely hindered the re-colonization by most benthic taxa resulting in a benthic community that was both poorly structured and scanty and with a small number of taxa, and whole groups of organisms, such as Mollusca, missing (Tesauro et al, 1995;Baudo et al, 2001a;Nocentini et al, 2001;Bielli and Tesauro, 2001).…”
Section: Study Areamentioning
confidence: 99%
“…1992) to 997 mg.kg -1 in 1996 (and the maximum values increased from 1978 to 2440 mg.kg -1 ) . Several toxicity tests ran in the years following liming (1992)(1993)(1994)(1995)(1996)(1997)(1998) confirmed that the sediments were contaminated enough to induce either a direct short term mortality or sublethal effects on crustacean species (Rossi and Beltrami, 1998;Beltrami et al, 1999;Barbero et al, 2001;Baudo et al, 2001b;Burton et al, 2001). This likely hindered the re-colonization by most benthic taxa resulting in a benthic community that was both poorly structured and scanty and with a small number of taxa, and whole groups of organisms, such as Mollusca, missing (Tesauro et al, 1995;Baudo et al, 2001a;Nocentini et al, 2001;Bielli and Tesauro, 2001).…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, according to previous studies, toxicity may exist for some species but not others (Burton et al 2001). Under our experimental conditions, the interaction between Cd and As was synergistic to the growth of both roots and shoots.…”
Section: Phytotoxic Effects Of Combined Metalsmentioning
confidence: 99%
“…Microtox® and Daphnia IQ toxicity tests are rapid screening assays that have shown good prediction with more standard acute toxicity bioassays (Hayes et al 1993;Toussaint et al 1995;Burton et al 2001). Evaluation of porewater toxicity can be informative because sediments integrate contaminant fluctuations over time (Nipper et al 2003).…”
Section: Bioassays (Microtox® and Daphnia Iq Tests)mentioning
confidence: 99%